The myth of scientific literacy - Shamos, Morris H. (Morris Herbert), 1917-2002. (New Brunswick, N.J. : Rutgers University Press, 1995)
Why do we make every schoolchild and college student take science? Does every American really need to be scientifically literate? In this provocative book, Morris Shamos, a physicist and science educator of very broad experience, argues that universal scientific literacy is a futile goal, and urges a critical review of the purpose of general education in science. Shamos argues that a meaningful scientific literacy cannot be achieved in the first place, and the attempt is a misuse of human resources on a grand scale. He is skeptical about forecasts of "critical shortfalls in scientific manpower" and about the motives behind crash programs to get more young people into the science pipeline. Finally, he is convinced that, as presently taught, the vast majority of students come out of science classes with neither an intellectual grasp nor a pragmatic appreciation of science.
Shamos advocates instead a practical science education curriculum that grants the impossibility of every American's learning enough science to make independent judgments about major scientific issues. Rather than giving children the heavy diet of scientific terms and facts they now get, he would emphasize: an appreciation of science as an ongoing cultural enterprise; an awareness of technology's impact on one's personal health, safety, and surroundings; and the need to use experts wisely in resolving science/society issues.
Includes bibliographical references (pages 239-251) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Science -- Study and teaching -- United States; Literacy -- United States; Sciences -- Étude et enseignement -- États-Unis.; Culture scientifique et technique -- États-Unis.; SCIENCE -- Study & Teaching; Literacy; Science -- Study and teaching; United States; Natuurwetenschappen; Onderwijs; Sciences - General; Physical Sciences & Mathematics